2014
DOI: 10.1016/j.jcin.2013.05.022
|View full text |Cite
|
Sign up to set email alerts
|

The LEVANT I (Lutonix Paclitaxel-Coated Balloon for the Prevention of Femoropopliteal Restenosis) Trial for Femoropopliteal Revascularization

Abstract: Treatment of femoropopliteal lesions with the low-dose Lutonix DCB reduced late lumen loss with safety comparable to that of control angioplasty. (LEVANT I, The Lutonix Paclitaxel-Coated Balloon for the Prevention of Femoropopliteal Restenosis; NCT00930813)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
260
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(277 citation statements)
references
References 25 publications
14
260
0
2
Order By: Relevance
“…In published randomized trials of femoropopliteal disease, [7][8][9][10] DCBs were generally studied in focal or short lesions, while long, complex disease or severe calcification were excluded to prevent primary angioplasty failure and to minimize bailout stenting.…”
Section: Introductionmentioning
confidence: 99%
“…In published randomized trials of femoropopliteal disease, [7][8][9][10] DCBs were generally studied in focal or short lesions, while long, complex disease or severe calcification were excluded to prevent primary angioplasty failure and to minimize bailout stenting.…”
Section: Introductionmentioning
confidence: 99%
“…[102] More recently, the Lutonix Paclitaxel-Coated Balloon for the Prevention of Femoropopliteal Restenosis (LEVANT I) trial demonstrated significantly decreased mean late lumen loss for de novo SFA disease treated with the lower paclitaxel dose Lutonix DCB versus conventional balloons in patients treated with either angioplasty only or after stenting. [103] The Drug-Eluting Balloon in Peripheral Intervention for The Superficial Femoral Artery trial randomizing patients to upfront DCB or conventional angioplasty followed by stenting demonstrate similarly encouraging results at 12 months. [104] Most studies of infrapopliteal revascularization include more CLI than IC patients, [105,106] and IC alone is an uncommon indication.…”
Section: Current Trends and Outcomes: Endovascular Management In Artementioning
confidence: 91%
“…DCB with adjunctive atherectomy may address some issues associated with stent placement in these segments even though flow-limiting dissections, recalcitrant recoil, or residual disease would still limit this approach. [82] Intermittent Claudication (IC) represents a progression of arterial obstruction caused by obstructive PAD causing ischemia. In contrast to both CLI and ALI the timing or need for revascularization in claudication is largely dictated by lifestyle limitation.…”
Section: Figure5 An Intraoperative Photograph Of a Right Femoral To mentioning
confidence: 99%
“…In one clinical study of a drug-coated balloon which allowed stratification to stent treatment, primary stenting was selected over balloon-only treatment for approximately 25% of patients [40], and in a registry of patients treated with a drug-coated balloon, 23% of patients also had a stent implanted [41]. Provisional stenting rates after acute percutaneous angioplasty (PTA) failure in the aforementioned and other recent clinical trials averaged approximately 13% [34,36,38,40,42]. In a study designed to compare efficacy of balloon-based PTA with that of a drugcoated stent, 50% of those patients who had been randomly assigned to the PTA arm received provisional stents [4].…”
Section: Expert Opinionmentioning
confidence: 99%